Comprehensive review on electrical noise analysis of TFET structures - Chander, Sweta; Sinha, Sanjeet Kumar; Chaudhary, Rekha (Superlattices and microstructures, 2022)
Tunnel Filed Effect Transistors (TFETs) have appeared as an alternative for conventional CMOS due to their advantages like very low leakage current and steep sub-threshold slope. In semiconductor devices, noise is considered an undesired signal that can deteriorate the desired signal. In TFET structures different noise sources affect the performance at different frequency ranges. This paper presents a comprehensive review of impact of electrical noise on the performance of various TFET structures. The impact of both low-frequency noise sources and high-frequency sources have been discussed thoroughly. The study of different types of electrical noises occur in simple TFET device and different structures of TFET is presented. •This review reported the impact of noise in Tunnel FET devices to understand the reliability issues.•The detail discussion has been done for the random telegraph noise, thermal noise, flicker noise, and shot noise for Si/Ge TFET and III-V TFETs.Recent research work for both low frequency as well high frequency noise for different TFET device design has been discussed in details.•The effect of noise for memory and circuit based on Tunnel FET devices as also been discussed.•The effect of noise on BTBT dominated current conduction in TFET and thermionic based current conduction has been presented in both device and circuit level.•The analytical models for noise analysis of different TFETs structures has also been reported.